EsKiMo II – the Eating study as a KiGGS Module in KiGGS Wave 2 - Mensink, Gert; Haftenberger, Marjolein; Brettschneider, Anna-Kristin; Barbosa, Clarissa Lage; Perlitz, Hanna; Patelakis, Eleni; Heide, Karoline; Frank, Melanie; Lehmann, Franziska; Krause, Laura; Houben, Robin; Butschalowsky, Hans; et al. (Robert Koch-Institut, Epidemiologie und Gesundheitsberichterstattung, 2017)
Nutrition plays an important role for health, in particular of children and adolescents. In addition to the baseline German Health Interview and Examination Survey for Children and Adolescents (KiGGS, 2003-2006), the nutrition survey EsKiMo (Eating study as a KiGGS Module) assessed the dietary habits of children and adolescents aged 6 to 17 in detail. In KiGGS Wave 2 (2014-2017) the corresponding module is EsKiMo II. Between June 2015 and September 2017, specially trained nutritionists will visit EsKiMo II participants at their homes. The parents of 6-to 11-year-olds are instructed on how to complete food records on four randomly chosen days - three consecutive days, followed later by an additional day. Participants aged 12 to 17 are interviewed personally on their food intake during the past four weeks with the dietary interview programme DISHES. Further information, for example, regarding dietary supplements is also recorded. EsKiMo II will provide an up-to-date and representative overview of the current nutrition status of 6-to 17-year-olds living in Germany, and it allows analysing changes in dietary behaviour over time. EsKiMo II can identify shortcomings in the nutrition of children and adolescents and thus may contribute with important information to nutrition and health policy.